Melatonin and its cross-talk with other signaling molecules under abiotic stress - Faizan, Mohammad; Sultan, Haider; Alam, Pravej; Karabulut, Fadime; Cheng, Shi-Hui; Rajput, Vishnu D.; Nie, Lixiao (Elsevier, 2024)
Melatonin is a hormone-like substance that serves as a secondary metabolite associated with a variety of physiological, hormonal, and natural processes at the cell, tissue, and organ levels. It acts as a plant biostimulant and increase tolerance against abiotic stresses like ssalinity, drought, heat, cold and heavy metals. Melatonin in plants, also called phytomelatonin, participating in the cellular mechanisms that ameliorates oxidative toxicity, hence helps the plant to stand abiotic stress conditions. These exclusive properties strengthen the defense capacity by stimulating the detoxification of reactive oxygen species (ROS), promoting physiological attributes, and activation of stress-responsive genes to ameliorate toxicity caused by abiotic stress. As a key molecule, it exhibits several important cellular and molecular interactions with nitric oxide (NO), calcium (Ca2+), hydrogen peroxide (H2O2) and hydrogen sulfide (H2S). In this review article, we discuss the salient role of melatonin in morphological and physiological adaptation of plant as well as its involvement in the abiotic stress mitigation. Besides, its role under stress, interaction of melatonin with NO, Ca2+, H2O2, and H2S has been demonstrated. This study will provide a reference for elucidating the regulatory mechanism of melatonin influencing the resistance to abiotic stress toxicity in plants.
Keywords: Melatonin; Drought stress; Cold stress; Hydrogen peroxide; Calcium